2023
DOI: 10.1002/advs.202304090
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Granular Hydrogels Functionalized with Aligned Architecture and Small Extracellular Vesicles Stimulate Osteoporotic Tendon‐To‐Bone Healing

Wei Song,
Zhijie Ma,
Xin Wang
et al.

Abstract: Osteoporotic tendon‐to‐bone healing (TBH) after rotator cuff repair (RCR) is a significant orthopedic challenge. Considering the aligned architecture of the tendon, inflammatory microenvironment at the injury site, and the need for endogenous cell/tissue infiltration, there is an imminent need for an ideal scaffold to promote TBH that has aligned architecture, ability to modulate inflammation, and macroporous structure. Herein, a novel macroporous hydrogel comprising sodium alginate/hyaluronic acid/small extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 96 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Dates from healing mouse flexor tendons has demonstrated that overactivation of the NF-κB signaling pathway enhanced the presence of proinflammatory macrophages at the injured area, resulting in elevated formation of scar tissue and disrupting the mechanical properties of the healing tendon ( 63 ). Additionally, an experimental study in a rat rotator cuff healing model displayed that inhibiting the NF-κB signaling pathway, deceased macrophage polarization toward M1 macrophages and thereby reduced the production of excessive inflammatory factors and finally provoked the regenerative potential of injured tissue ( 64 ). Previous reports have indicated that microRNAs (miRNAs) primarily function as a silencer of coding genes and that the expression of miRNAs is thought to play a significant role in injured tissue’s healing process.…”
Section: The Mechanisms Of Nf-κb In Tendon Fibrotic Scar Healing Adhe...mentioning
confidence: 99%
“…Dates from healing mouse flexor tendons has demonstrated that overactivation of the NF-κB signaling pathway enhanced the presence of proinflammatory macrophages at the injured area, resulting in elevated formation of scar tissue and disrupting the mechanical properties of the healing tendon ( 63 ). Additionally, an experimental study in a rat rotator cuff healing model displayed that inhibiting the NF-κB signaling pathway, deceased macrophage polarization toward M1 macrophages and thereby reduced the production of excessive inflammatory factors and finally provoked the regenerative potential of injured tissue ( 64 ). Previous reports have indicated that microRNAs (miRNAs) primarily function as a silencer of coding genes and that the expression of miRNAs is thought to play a significant role in injured tissue’s healing process.…”
Section: The Mechanisms Of Nf-κb In Tendon Fibrotic Scar Healing Adhe...mentioning
confidence: 99%